HEAT TOLERANCE INDEX IN DAIRY GOATS: CLASS REPORT (Environmental Smoke, 2024)
To evaluate the influence of the environment on the behavioral and physiological parameters of Saanen and alpine brown goats, disciplinary work was carried out in which a field experiment was conducted, in the municipality of Lajes do Cabugi, Rio Grande do Norte, on the Três property. Brothers, which is a dairy goat production farm. The adaptation of animals to the breeding environment is an important factor for them to have good health and achieve greater productivity, which is one of the objectives of the action of veterinarians, acting preventively (SOUZA et al., 2010; LOPES et al., 2012). When academics participate in pedagogical activities, they develop and prepare more completely for professional life. During the pedagogy, two specimens of each breed were used and observed over a 90-day interval. The following sequence of observations was adopted: 1st observation carried out at 9 am and the 2nd observation was carried out at 3 pm. All animals were female and carried out their normal grazing activities. The animals had access to pasture under identical conditions, as well as access to nutritional supplementation when they returned to the pen at night. The rectal and environmental temperature variables were recorded at 9:00 am and 3:00 pm, and these were used by applying them in the ITC formula (1.0 ta – 20 d +60) (FERREIRA, 2011). The average results obtained were 32.67ºC for room temperature; rectal temperature of the Saanen and alpine brown in the morning and afternoon, respectively, were 40.18ºC and 39.95ºC in the morning; 39.8ºC and 39.75ºC in the afternoon. It was concluded, with the results obtained during the field classes, that the Saanen presented better results compared to the alpine brown for the edaphoclimatic conditions of the property where the research work was carried out. Pedagogically, this activity carried out in the field increases the learning efficiency of veterinary medicine students and favors their better training, reflecting the community's desires and everyone's well-being.